Factors associated with satisfaction of inpatient psychiatric care: a cross country comparison. Issue 2 (30th January 2020) - Bird, Victoria; Miglietta, Elisabetta; Giacco, Domenico; Bauer, Michael; Greenberg, Lauren; Lorant, Vincent; Moskalewicz, Jacek; Nicaise, Pablo; Pfennig, Andrea; Ruggeri, Mirella; Welbel, Marta; Priebe, Stefan
Abstract: Background: Patient satisfaction is a key indicator of inpatient care quality and is associated with clinical outcomes following admission. Different patient characteristics have been inconsistently linked with satisfaction. This study aims to overcome previous limitations by assessing which patient characteristics are associated with satisfaction within a large study of psychiatric inpatients conducted across five European countries. Methods: All patients with a diagnosis of psychotic (F2), affective (F3) or anxiety/somataform (F4) disorder admitted to 57 psychiatric inpatient units in Belgium, Germany, Italy, Poland and the UK were included. Data were collected from medical records and face-to-face interviews, with patients approached within 2 days of admission. Satisfaction with inpatient care was measured on the Client Assessment of Treatment Scale. Results: Higher satisfaction scores were associated with being older, employed, living with others, having a close friend, less severe illness and a first admission. In contrast, higher education levels, comorbid personality disorder and involuntary admission were associated with lower levels of satisfaction. Although the same patient characteristics predicted satisfaction within the five countries, there were significant differences in overall satisfaction scores across countries. Compared to other countries, patients in the UK were significantly less satisfied with their inpatient care. Conclusions: Having a better understanding of patient satisfaction may enable services to improve the quality of care provided as well as clinical outcomes for all patients. Across countries, the same patient characteristics predict satisfaction, suggesting that similar analytical frameworks can and should be used when assessing satisfaction both nationally and internationally.